Deep space optical communications (Wiley-Interscience, 2006)
This book captures a quarter century of research and development in deep space optical communications from the Jet Propulsion Laboratory (JPL). Additionally, it presents findings from other optical communications research groups from around the world for a full perspective. Readers are brought up to date with the latest developments in optical communications technology, as well as the state of the art in component and subsystem technologies, fundamental limitations, and approaches to develop and fully exploit new technologies.